A synergistic effect of albumin and H2O2 accelerates corrosion of Ti6Al4V. (15th October 2015) - Yu, Fei; Addison, Owen; Davenport, Alison J.
Graphical abstract: Abstract: The synergistic effect of albumin and H2 O2 on corrosion of titanium alloy Ti6Al4V in physiological saline was investigated with long-term immersion tests and electrochemical methods. It was found that in the presence of both albumin and H2 O2, the rate of metal release in immersion tests was far higher than in the presence of either species alone. Electrochemical polarisation curves and potentiostatic tests showed that H2 O2 increased both the rates of the anodic and cathodic reactions, whilst albumin significantly decreased the rate of the cathodic reaction and slightly decreased the rate of the anodic reaction. The synergistic effect of albumin and H2 O2 during immersion tests was attributed to the effect of adsorption of albumin in lowering the rate of the cathodic reaction and thus lowering the open circuit potential into the active region of titanium where complexation by H2 O2 increased the corrosion rate. The corrosion attack was found to be greater in the β-phase of the alloy. The findings suggest that current standard tests in physiological or phosphate-buffered saline may underestimate the rate of corrosion in the peri-implant environment, in which albumin is the predominant protein, and reactive oxygen species such as H2 O2 can occur as a result of inflammatory reactions in response to surgery, infection, or implant corrosion products. Statement of significance: Corrosion of many biomedical implant materials occurs in the body leading to adverse biological responses. Several components of the environment into which a metal implant is placed including proteins and products of cellular physiology, been shown to modify corrosion resistance. Previously all studies on such components including the common protein albumin and the inflammatory product H2 O2 have considered the effects of these species in isolation. For the first time we report a synergistic interaction between albumin and H2 O2 significantly accelerating corrosion of Ti6Al4V at physiological pH and temperature. This is attributed to an increased rate of the anodic reaction caused by H2 O2 complexation of Ti, suppression of cathodic reaction by albumin adsorption shifting OCP to the active region of Ti6Al4V.